COMPARISON OF THE POTENCY OF SEVERAL FLUORIDE-BASED VARNISHES AS AN ANTICARIOGENIC ON CALCIUM, PHOSPHATE, AND FLUORIDE ION LEVELS - Soekanto, Sri Angky; Rosithahakiki, Namira; Suniarti, Dewi Fatma; Sahlan, Mohamad (International Journal of Applied Pharmaceutics, 2018)
Objectives: The purpose of this present study was to analyze several fluoride-based varnishes: Silver diamine fluoride (SDF), nanosilver fluoride (NSF), and propolis fluoride (PPF). Fluoride-based varnish is proven to act as antibacterial and remineralization agents that arrested caries progression with minimal side effects. SDF, the golden standard for this study, was compared to NSF and PPF, which were made in our own laboratory, to evaluate their ability to release calcium, phosphate, and fluoride ions and act as anticariogenic agents. Methods: Human dentin discs were prepared and divided into control groups and treatment groups with SDF (38%), NSF (3.16%, 3.66%, and 4.16%), and PPF (3%, 6%, and 10%). The dentin discs were demineralized using a demineralization solution (pH 4.4) for 96 h. Each dentin disc in the treatment group received a topical application of various fluoride-based varnishes and then was subjected to pH-cycling for 8 days. The quantity of calcium, phosphate, and fluoride ions on the dentin discs surface was compared after being detected using energy dispersive X-ray spectroscopy. Results: The result revealed that the calcium ion levels in groups NSF and PPF increased significantly compared to SDF. The levels of phosphate ions and fluoride ions in groups NSF and PPF increased significantly compared to SDF. Conclusion: The study concluded that, in contrast to SDF, the prepared NSF and PPF fluoride-based varnishes were shown to release calcium, phosphate, and fluoride ions in this study. Hence, NSF and PPF fluoride-based varnishes are promising as anticariogenic agents.